Artificial Intelligence Based Intruder Detection Home Security System - Pasha, M. Jahir; Shankar, B. Maruthi; Sivakumar, S. A.; Aswin, S.; Bragadeesh, A.; Deepak, S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
An effective face detection and identification algorithm is required to design a highly effective intruder detecting surveillance system. When a person is captured on camera, CNN, an artificial intelligence programme that detects objects, and Grassmann’s algorithm are utilised to determine whether or not the individual is an invader. The research’s objective is to identify the quickest method for homeowners to be notified if a burglar or intruder breaks into their house utilising a proactive surveillance system. This device’s programming was based on several recognition algorithms and a framework for evaluating factors that might distinguish between intruders and burglars. Developmental research was employed in the design to address the research topic. The outcome demonstrates that the system is capable of spotting and identifying burglars and can inform the homeowners in advance via email and emergency alarms. The technology can identify intruders, alert the family members in advance, and activate the home’s alarm system, it is determined